1987
DOI: 10.1080/02652038709373614
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis inhibition and cardiac lesions associated with deoxynivalenol ingestion in mice

Abstract: Deoxynivalenol (DON), an occasional contaminant of foodstuffs, has been implicated in outbreaks of mycotoxicosis. Balb-c mice that had ingested 0.35 mg/kg of DON showed a drastic decrease in food intake and concomitant loss of weight. Severe depletion of the lymphoid organs and liver were also observed. Cardiac lesions, appeared as calcified pericarditis foci in young animals fed a diet contaminated by 10 to 20 ppm of DON for a period of a few weeks. DON inhibited protein synthesis. This inhibition occurred at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
0
14
0
1
Order By: Relevance
“…No effects of feeding DON with respect to either an increase in the serum concentration of IgA or the development of signs of intestinal inflammation was detected in these horses, which suggests that this species may not be affected by DON ingestion at these levels. 3,7,15,20 Feed refusal, which has been reported 20 in susceptible species, was not detected in these horses. Although the horses were not weighed at the conclusion of the study, they had all clearly gained weight and had improved body condition.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…No effects of feeding DON with respect to either an increase in the serum concentration of IgA or the development of signs of intestinal inflammation was detected in these horses, which suggests that this species may not be affected by DON ingestion at these levels. 3,7,15,20 Feed refusal, which has been reported 20 in susceptible species, was not detected in these horses. Although the horses were not weighed at the conclusion of the study, they had all clearly gained weight and had improved body condition.…”
mentioning
confidence: 86%
“…3 Deoxynivalenol has been given the trivial name vomitoxin because it causes emesis when ingested by swine and dogs. 21 Other clinical effects attributed to the toxic effects of ingested DON include feed refusa1, 20,23 decreased weight gain, 6,7,20 signs of gastrointestinal irritation (e.g., diarrhea, colic, rectal prolapse, hematochezia), 3,7,15 thickening of the squamous aspect of the gastric lining of pigs, 16 reproductive problems, 7 skin irritation, 3,7 cardiotoxicity, 15 and interference with the immune system. 16 The extent to which DON causes clinical signs of toxicosis is proportional to its concentration in contaminated feed.…”
mentioning
confidence: 99%
“…This fi nding indicates that DON administration takes time to produce an arrhythmogenic condition in the rat heart. In a previous study in which the protein levels in the heart, liver, kidneys, and spleen were evaluated in mice that had been intraperitoneally injected with DON and sacrifi ced 5 hr later, it was found that DON with a dose of 20 or 80 mg/kg causes metabolic damage to myocytes by inhibiting protein synthesis in mice (Robbana-Barnat et al, 1987). This study also demonstrated the histological changes represented by pericardial calcifi cations observed in most mice after 15 or 21 days of 20 ppm -DON ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that some trichothecenes possess potent cardiac toxicity. However, there is little evidence about the cardiac effects of DON, although cardiac lesions combined with calcified pericarditis were caused by the ingestion of a diet containing 10 to 20 ppm of DON for a few weeks (Robbana-Barnat et al, 1987). Therefore, it is necessary to clarify whether DON has…”
Section: Introductionmentioning
confidence: 99%
“…In an incorporation study with mice, the 14 C leucine incorporation into the liver was decreased at 20 mg DON/kg feed. It was assumed that DON inhibited the protein synthesis, and therefore the reduction of the 14 C leucine amount occurred (Robbana-Barnat et al, 1987). The addition of 0.5 and 5 mg DON/ml to Caco-2 cells led to a decreased [ 3 H] leucine incorporation and a parallel decrease of cellular protein content (De Walle et al, 2010).…”
Section: Nutrient Transportmentioning
confidence: 99%